PENGARUH MEDIA PLOTAGON TERHADAP HASIL BELAJAR SISWA KELAS V PADA MATA PELAJARAN IPA MATERI KALOR DI SDN CIBUNTU 01 - Syafira Eka Nurhaura; Zulfadewina Zulfadewina (Prodi PGMI FTK UIN Ar-Raniry Banda Aceh bekerjasama dengan PW PERGUNU Aceh, 2022)
The development of education in Indonesia is undergoing rapid changes, therefore we as Indonesian citizens must prepare ourselves so as not to be out of date. In the teaching and learning process sometimes there are students who feel bored and bored when the lesson takes place so that they have difficulty in understanding the material presented by the teacher and cause low student learning outcomes. This study aims to determine whether or not plotagon media has an effect on the learning outcomes of fifth graders at SDN Cibuntu 01. The sample in this study was class V at SDN Cibuntu 01 which consisted of 2 groups of data, namely the experimental class of 27 students and the control class of 25 students. The instrument in this study used a learning outcomes test sheet in the form of multiple choice. The experimental design used in this study was the Posttest-Only Control Design method. Data analysis used independent sample t-test. It is obtained that the value of sig. 0.000 < 0.05 of Sig.(2-tailed). So it can be concluded that plotagon media can affect the value of student learning outcomes at SDN Cibuntu 01.